Isolation of Nematophagous Fungi from Lau Kawar Lake, North Sumatra, Indonesia. Issue 1 (March 2021) - Hastuti, L D S; Yurnaliza, Y; Tarigan, W E; Hartanto, A; Pahlevi, S
Abstract: Root-knot nematodes are harmful organisms which cause severe damage to plants and decreasing its productivity. Biocontrol agents isolated from potential environment may solve the intriguing problem of these nematodes. Nematophagous fungi has proven as promising strategy in controlling nematodes when compared to commercial pesticides which may pollute the soil and environment through accumulated residues post-usage. Nematophagous fungi were isolated from several soils or sediments around Lau Kawar Lake using a combination of pour and sprinkle techniques. Nine fungal morphotypes were recovered from soil/sediment samples as revealed from their distinctive morphologies. Two isolates, LK.10.1 and LK.10.3 were designated as potential nematophagous fungal isolates by their effectiveness in killing nematodes within 36 hr of observation. Species-level identification is currently carried out for the isolates to reveal and confirm their identities as nematophagous fungi.